A NEW FRACTIONAL MODEL AND OPTIMAL CONTROL TO MODEL CHAOTIC PROBLEMS - Chen, Johnny; Chen, Timothy; Daleanu, Bunnitru; Chan, Tim; Souissi, Doukaima; Oksendal, Lucian (Institute of Advanced Engineering and Science, 2020)
The point of the article is to plan a productive mathematical technique to illuminate a class of time partial ideal control issues. In this issue definition, the fragmentary subordinate administrator is considered in three events with both solitary and non? particular pieces. The fundamental provisions are determined for the optimality of certain issues and the advanced technique is assessed for various decisions of subsidiary administrators. An optimal control strategy for studying the results on the proposed control model is also utilized. Recreation results show that the proposed procedure functions admirably and master vides tasteful outcomes with extensively less computational time than the other existing strategies. The contribution of their study is that Near outcomes likewise check that the partial administrator with Mittag? Leffler piece in the Caputo sense enhances the execution of these controlled frameworks as far as the transient reaction contrasted with the other fragmentary and whole number subordinate administrators.